Carbon tax: Characterization of research - Dias, P.; Rocha, A. (Taking on climate change through green taxation, 2023)
One of the main climatic concerns is the increase of CO2 concentrations in the atmosphere. In the attempt and need to combat this problem, several regulatory policies have been applied in several countries by the governments, with the carbon tax being one of the most economical and effective policies in reducing CO2 emissions, thus leading to an increase in scientific research on this topic. Therefore, the main objective of this study is characterizing the existing research on the theme Carbon Tax. A sample of 121 scientific articles was collected, where several characteristics related to the content of published articles and respective authors were subsequently identified. The results obtained reveal that the number of publications has been increasing, and the themes most related to this investigation are: cap-and-trade, carbon dioxide emissions, climate change, computable general equilibrium (cge) model and emissions. Regarding the profile of researchers, the type of collective authorship is the most common and the country with the most affiliated authors is China.